An implicit enumeration algorithm for complex scheduling problems - FLORIAN, M.; TILQUIN, C.; TILQUIN, G. (International journal of production research, 1975)
Several algorithms have been presented for handling complex scheduling problems. These methods are computationally impractical when confronted with large problems. New algorithms have been developed for solving job-shop problems. They are more efficient than the previous ones because they use dominance and better bound ideas. The purpose of this paper is to present an efficient algorithm for complex scheduling problems generalizing those ideas.